Impulse Control Disorders: Updated Review of Clinical Characteristics and Pharmacological Management - Grant, Jon E.; Schreiber, Liana R.; Odlaug, Brian L. (Frontiers in Psychiatry, 2011)
Impulse control disorders (ICDs) are characterized by urges and behaviors that are excessive and/or harmful to oneself or others and cause significant impairment in social and occupational functioning, as well as legal and financial difficulties. ICDs are relatively common psychiatric conditions, yet are poorly understood by the general public, clinicians, and individuals struggling with the disorder. Although ICD treatment research is limited, studies have shown ICDs may respond well to pharmacological treatment. This article presents a brief overview about the clinical characteristics of ICDs and pharmacological treatment options for individuals with ICDs.